Promotional strategy and Prices as well as Distribution channels On Sales Performance In PT Alva Mountindo Medan - Maya Putra, Muhamad Umar; Agustina, Tri Leni; Nurainun, Nurainun (Institute of Computer Science (IOCS), 2024)
The purpose of this research is to determine the effect of promotional strategies, prices and distribution channels on increasing sales at PT Alva Mountindo Medan. The sample for this research was consumers of PT Alva Mountindo Medan with 56 sample respondents used.The data used is primary data, this research analyzes the relationship between promotional strategies, prices and distribution channels on increasing sales. The statistical method used is multiple linear regression (multilinear regression analysis) with a quantitative approach using classical assumption tests first.The results of this research show that partially the promotional strategy variable (X1) has a positive and significant effect on sales (Y), indicated by the value of tcount 2.873 > ttable 2.00665 with a significance of 0.007 < 0.05. Partially, price (X2) has a positive and significant effect on sales (Y), indicated by the value of tcount 2.919 > ttable 2.00665 with a significance of 0.005 < 0.05. Partially, the distribution channel (X3) has a positive and significant effect on sales (Y), indicated by the value of tcount 2.771 > ttable 2.00665 with a significance of 0.008 < 0.05. Meanwhile, simultaneously both promotional strategies (X1), prices (X2) and distribution channels (X3) have a positive and significant effect on sales with a Fcount value of 36.356 > Ftable 2.78 with a significance of 0.000 < 0.05.).